2016
DOI: 10.1149/2.0201613jes
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Rich Transition Metal Diborides as Electrocatalysts for Hydrogen Evolution Reactions in a Wide Range of pH

Abstract: Solid solutions of HfB 2 -ZrB 2 mixtures were prepared by high-energy ball milling of diboride and additive powders followed by spark plasma sintering (SPS). A mixture of stoichiometric 1:1 HfB 2 -ZrB 2 borides was the base composition to which Hf, Zr, Ta, LaB 6 or Gd 2 O 3 was added. Hf, Zr and Ta were added in order to bring the boron-to-metal ratio down to 1.86, rendering the boride as MeB 1.86 . In the case of LaB 6 and Gd 2 O 3 , 1.8 mol% was added. Electroanalytical behavior of hydrogen evolution reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…Commercial acidic proton‐exchange‐membrane electrolyzers utilize Pt/C catalysts, but the scarcity of Pt greatly limits the large‐scale application; alkaline electrolyzers use low‐cost Ni catalysts, but suffer from low efficiency and corrosion . Consequently, active, cost‐effective, and robust electrocatalysts for hydrogen evolution reaction (HER) have been intensively pursued, such as metal‐free catalysts, single‐atom catalysts, transition‐metal chalcogenides, borides, carbides, nitrides, and phosphides (TMPs) . In particular, the easily adjustable electronic structure and surface properties of TMPs due to under‐coordinated P atoms, permit facile manipulation of HER performance .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Commercial acidic proton‐exchange‐membrane electrolyzers utilize Pt/C catalysts, but the scarcity of Pt greatly limits the large‐scale application; alkaline electrolyzers use low‐cost Ni catalysts, but suffer from low efficiency and corrosion . Consequently, active, cost‐effective, and robust electrocatalysts for hydrogen evolution reaction (HER) have been intensively pursued, such as metal‐free catalysts, single‐atom catalysts, transition‐metal chalcogenides, borides, carbides, nitrides, and phosphides (TMPs) . In particular, the easily adjustable electronic structure and surface properties of TMPs due to under‐coordinated P atoms, permit facile manipulation of HER performance .…”
Section: Introductionmentioning
confidence: 99%
“…Cation and anion vacancies, have been investigated in electrocatalytic HER, because their ability to modify electronic structures of catalytic sites would optimize the hydrogen adsorption free energy (Δ G H ). For example, boron vacancies (Bv) have been reported to change the lattice parameters of HfB 2 ‐ZrB 2 and possibly introduce more electrons at the Fermi level to facilitate HER . While nitrogen vacancies (Nv) created in Ni 3 N 1− x can increase the electron density of Ni atoms next to Nv and downshift the d‐band center to strengthen the water adsorption and tune the adsorption–desorption behavior of intermediate H* during HER .…”
Section: Introductionmentioning
confidence: 99%
“…According to the open literatures, only a few examples of transition metal borides or transition metal-boron alloys have been investigated over the past decades in terms of electrocatalytic properties towards the HER. [20][21][22][23][24][25][26][27][28][29][30] It was found that the binary NiÀB and CoÀB typically showed high activities towards the HER, which compare favorably with other types of transition metal compounds. These findings inspired us to explore the full potential of transition metal borides or transition metal-boron alloys as non-noble electrocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…The potential of transition metal borides or transition metal‐boron alloys as HER catalyst is still largely underexplored. According to the open literatures, only a few examples of transition metal borides or transition metal‐boron alloys have been investigated over the past decades in terms of electrocatalytic properties towards the HER . It was found that the binary Ni−B and Co−B typically showed high activities towards the HER, which compare favorably with other types of transition metal compounds.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Commercial acidic proton-exchange-membrane electrolysers utilize Pt/C catalysts, but the scarcity of Pt greatly limits the large-scale application; [2] alkaline electrolysers use low-cost Ni catalysts, but suffer from low efficiency and corrosion. [3] Consequently, active, costeffective and robust electrocatalysts for hydrogen evolution reaction (HER) have been intensively pursued, such as metalfree catalysts, [4] single atom catalysts, [5] transition metal chalcogenides, [6] borides, [7] carbides, [8] nitrides, [9] and phosphides (TMPs). [10] Especially, the easily adjustable electronic structure and surface properties of TMPs due to under-coordinated P atoms, permit facile manipulation of HER performance.…”
Section: Introductionmentioning
confidence: 99%